A study of clinico-microbiological profile of surgical site infections in a tertiary care hospital - Kochhal, Niharika; Mudey, Gargi Dangre; Choudhari, Sonali Zadbuke (International Journal of Advances in Medicine, 2019)
Background: Surgical Site Infection (SSI) is the 3rd most commonly reported infection accounting for 14-16% of all Health care associated infections among hospitalized patients. Surgical Site Infections are responsible for an increased economic burden to healthcare systems, including additional postoperative hospital stay and costs. The present study was conducted in a tertiary care hospital to study the incidence, risk factors and associated pathogens of Surgical Site Infection. Methods: A total of 100 patients operated of clean and clean-contaminated surgeries from Orthopaedics, Surgery and Obstetrics and Gynaecology Department of AVBRH, Sawangi were included. Results: Overall infection rate was 6%. Patients in the age of above 71 years showed maximum rate of infection (14.28%) followed by 61 to 70 years (10%) and 51-60 years (10%). Surgical site infection rate was 4.65% (2/43) in clean operative wounds and 7.02% (4/57) in clean contaminated operative wounds. Escherichia coli and Klebsiella pneumonia were the most common organisms causing SSI. None of the risk factor was found significantly associated with the development of SSI. Conclusions: This study gave a better understanding of microbial pathogens of our institute which may have epidemiological and therapeutic implications. It will act as a pilot study to conduct further such larger research.